DAMPAK KOMUNIKASI POSITIF DAN NEGATIF PADA REMAJA DI ERA PENGGUNAAN MEDIA SOSIAL - Saniah, Nurul (Journal Of Law And Social Society, 2025)
In the use of social media for all groups is very diverse. Social media has a great impact on its users. Social media is used to communicate, get information, express themselves and so on. The use of social media can cause positive and negative communication in adolescents. The impact of positive communication in adolescents can connect with family even though the distance between the two is far. In addition, social media is a source of information that is broad and easy to access wherever we are. Teenagers can learn various current news topics to school information. Providing space for teenagers to express themselves and show their talents through various visual, audio-visual and written content. The impact of negative communication on excessive use of social media can increase the risk of depression, anxiety, and sleep disorders. Social pressure that can compare yourself to others on social media. Increasing cyberbulling, body shaming, and online fraud. In addition, the use of social media becomes a dependency and addiction so that many teenagers spend their time using social media so that it hinders learning, working and interacting directly with others. The purpose of writing this scientific article is to determine the impact of positive and negative communication on adolescents, especially adolescents who are still in school.